The impact of economic reforms on health indicators in Guyana - Gafar, John (2005)
Examines the performance of the health indicators in Guyana during the period of economic reforms. Describes briefly the health care system and examines the allocation of resources to the health sector. Looks at the immunization and malnutrition rates and focuses on the trend and determinants of the health indicators.